STRATEGI GURU PENDIDIKAN AGAMA ISLAM MEMBANGUN KARAKTER DISIPLIN DAN RELIGIUS SISWA - Berlinda Rahmadani; Nurul Latifatul Inayati (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2023)
The existence of the era of globalization affects the morale of students to experience changes. Many students at Muhammadiyah 2 Karanganyar Vocational School come late to school, play truant, and even commit mischief at school.Therefore it is necessary to have character education to shape the disciplinary and religious character of students. Islamic Religious Education teachers play an important role in shaping the disciplinary and religious character of students. Therefore, researchers want to find out the methods or strategies of teachers, especially Islamic Religious Education Teachers, in instilling the disciplinary and religious character of students at SMK Muhammadiyah 2 Karanganyar. The purpose of this research is to describe how the Islamic Religious Education Teacher's strategy is in instilling the discipline and religious character of students. The type of research used is Field Research with a phenomenological approach. To check the validity of the data obtained by researchers using data source triangulation and theory triangulation. The data analysis technique uses the Miles and Hubermen models, namely data reduction, data presentation, and drawing conclusions. In the research that has been carried out, the strategy carried out by Islamic Religious Education Teachers in shaping the discipline and religious character of students is to provide habituation to students, provide good examples to students, provide sanctions to students who break the rules, make students comfortable. in class and giving advice after midday prayers in congregation.